Late Holocene vegetation dynamics and deforestation in Rano Aroi: Implications for Easter Island's ecological and cultural history. (15th October 2015) - Rull, Valentí; Cañellas-Boltà, Núria; Margalef, Olga; Sáez, Alberto; Pla-Rabes, Sergi; Giralt, Santiago
Abstract: Easter Island (Rapa Nui) has been considered an example of how societies can cause their own destruction through the overexploitation of natural resources. The flagship of this ecocidal paradigm is the supposed abrupt, island-wide deforestation that occurred about one millennium ago, a few centuries after the arrival of Polynesian settlers to the island. Other hypotheses attribute the forest demise to different causes such as fruit consumption by rats or aridity but the occurrence of an abrupt, island-wide deforestation during the last millennium has become paradigmatic in Rapa Nui. We argue that such a view can be questioned, as it is based on the palynological study of incomplete records, owing to the existence of major sedimentary gaps. Here, we present a multiproxy (pollen, charcoal and geochemistry) study of the Aroi core, the first gap-free sedimentary sequence of the last millennia obtained to date in the island. Our results show changing vegetation patterns under the action of either climatic or anthropogenic drivers, or both, depending on the time interval considered. Palm forests were present in Aroi until the 16th century, when deforestation started, coinciding with fire exacerbation –likely of human origin– and a dry climate. This is the latest deforestation event recorded so far in the island and took place roughly a century before European contact. In comparison to other Easter Island records, this record shows that deforestation was neither simultaneous nor proceeded at the same pace over the whole island. These findings suggest that Easter Island's deforestation was a heterogeneous process in space and time, and highlights the relevance of local catchment traits in the island's environmental and land management history. Graphical abstract: Highlights: We present the first complete Easter Island's record (Aroi) for the last millennia. Vegetation dynamics was influenced by both climatic and anthropogenic drivers. The Aroi deforestation, the latest recorded so far (AD1520), was likely due to humans. Island's deforestation was not simultaneous and abrupt but heterogeneous in time and space. Ecocidal and genocidal theories of cultural collapse are not supported by our data.